2023
DOI: 10.1007/s40279-023-01836-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Biomarkers for Managing Workload in Athletes: Considerations and Recommendations for Evidence-Based Use of Established Biomarkers

Abstract: Blood-based biomarkers can provide an objective individualized measure of training load, recovery, and health status in order to reduce injury risk and maximize performance. Despite enormous potentials, especially owing to currently evolving technology, such as point-of-care testing, and advantages, in terms of objectivity and non-interference with the training process, there are several pitfalls in the use and interpretation of biomarkers. Confounding variables such as preanalytical conditions, inter-individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 154 publications
(172 reference statements)
2
19
0
Order By: Relevance
“…At the explicit express of the coaches of the team studied, we did not perform any further objective measures, although it would have been interesting to additionally examine muscle function, for example, during the countermovement jump or the squat jump, as Perkins et al 15 did in their study. In the present study, CK showed characteristics consistent with the literature on athletes: significantly higher values after several days of intense exercise than after an average of 40 hours of rest, 14,21 significant interindividual variability, 14,21,22 and the repeated-bout effect during the preseason. 14,21 Thus, our hypothesis about the behavior of CK in relation to the current recovery-stress state in these handball players was confirmed.…”
Section: Biochemical Monitoring Of Handball Players Using Cksupporting
confidence: 91%
See 2 more Smart Citations
“…At the explicit express of the coaches of the team studied, we did not perform any further objective measures, although it would have been interesting to additionally examine muscle function, for example, during the countermovement jump or the squat jump, as Perkins et al 15 did in their study. In the present study, CK showed characteristics consistent with the literature on athletes: significantly higher values after several days of intense exercise than after an average of 40 hours of rest, 14,21 significant interindividual variability, 14,21,22 and the repeated-bout effect during the preseason. 14,21 Thus, our hypothesis about the behavior of CK in relation to the current recovery-stress state in these handball players was confirmed.…”
Section: Biochemical Monitoring Of Handball Players Using Cksupporting
confidence: 91%
“…For this reason, CK is considered an important marker for the assessment of muscular stress and recovery and is widely used in sports medicine, research, and sports practice. [12][13][14] The short-term response of CK to training or match load and long-term changes over the course of a season have also been investigated in high-level handball players. 16,19,20 Therefore, we decided to use the biomarker CK as an objective measure to assess muscle stress and recovery in this observational study.…”
Section: Biochemical Monitoring Of Handball Players Using Ckmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe myofibrillar damage, particularly as it occurs after unaccustomed eccentric exercise bouts, usually results in significant increases in CK, LDH and MYO, which have been extensively used as indirect biomarkers to monitor the extent of acute stress as well as recovery ( 35 ). The activity of both cytosolic enzymes (CK, LDH) during a nine ( 10 ) and 33-day ( 13 ) CP supplementation period was not lower compared to a placebo after muscle-damaging exercise, which could have indicated either reduced acute muscle stress or accelerated reconstruction of damaged tissue.…”
Section: Discussionmentioning
confidence: 99%
“…-Biochemical markers, including creatine kinase (CK), urea, uric acid, ammonia, blood lactate, and plasma glutamine, have undergone extensive study across various athletes [57,58]. These markers are already used in many areas of sport to evaluate an athlete's training response, helping coaches to identify workload and prevent injuries [59]. CK activity reflects both the intensity and volume of exercise.…”
Section: Uncovering Ots Markers: Biochemical Immunological and Hormon...mentioning
confidence: 99%